2002
DOI: 10.1097/00002030-200210180-00004
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Epstein-Barr virus- and HIV-specific CD27− CD8+ T cells is associated with progression to viral disease in HIV-infection

Abstract: Taken together, our data indicate that virus-specific CD27- T cells may be important effector T cells in controlling chronic viral infections in humans and that lack of differentiation into CD27- effector T cells may lead to progression of viral disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
4
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 37 publications
3
69
4
1
Order By: Relevance
“…In contrast, after infection with LCMV the majority of gp33-specific CTL retained CD27 expression. The retained CD27 expression on memory CTL following infection with LCMV was unexpected since T cell proliferation and differentiation to effector cells has been correlated with loss of CD27 expression [10,14,23]. To further substantiate our observation, memory CTL specific for different LCMV antigens were analyzed 100 days after infection in secondary lymphoid organs and in the circulation.…”
Section: Cd27 Expression On Memory Ctlsupporting
confidence: 59%
See 1 more Smart Citation
“…In contrast, after infection with LCMV the majority of gp33-specific CTL retained CD27 expression. The retained CD27 expression on memory CTL following infection with LCMV was unexpected since T cell proliferation and differentiation to effector cells has been correlated with loss of CD27 expression [10,14,23]. To further substantiate our observation, memory CTL specific for different LCMV antigens were analyzed 100 days after infection in secondary lymphoid organs and in the circulation.…”
Section: Cd27 Expression On Memory Ctlsupporting
confidence: 59%
“…Therefore, the differentiation of the memory CTL population may reflect unique properties of the particular viral infection. Persistent CD27 expression has been associated with impaired effector function of EBV-and HIV-specific CTL [10,13,14]. However, in vitro work and recent studies in recombinant mice have provided evidence that the CD27-CD70 interaction provides a costimulatory signal to T cells [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…10,22 In these studies, virus-specific CD8 ϩ T cells accumulate in the CD45R0 ϩ CD27 ϩ CCR7 Ϫ subset and display none of the features normally associated with cytotoxic effector function. The finding that a direct correlation exists between number and phenotype of virus-specific CD8 ϩ T cells and the level of plasma viral load 23,24 corroborates that functional maturation of CD8 ϩ T cells is of prime importance in maintaining viral latency.…”
Section: Introductionmentioning
confidence: 62%
“…Finally, the last hypothesis, which is the one that we favor, is that CMV-specific T lymphocytes are not fully functional in fetuses. In line with this interpretation, an increased number of studies concluded to impaired function of CD8 ϩ T cells based on data showing a dissociation between the number of CD8 ϩ T cells primed with viruses and the number of T cells that respond to the corresponding viral antigens by IFN-␥ production (23)(24)(25)(26). Comparing IFN-␥ responses with CMV during primary infection in both fetuses and adults should definitely demonstrate whether CD8 response to CMV is less intense in early age.…”
Section: Discussionmentioning
confidence: 97%